Influence of tour guides on the quality of service at the San Francisco Convent Museum - García Chumioque, Florisa (2020)
Any type of service without a dose of quality is difficult to meet or exceed the expectations of the customer or visitor, this kind of situation results in customers or visitors not returning or recommending the service, all this signifying economic deficiencies as a result of a bad service. The present research aims to “Identify what type of relationship and influence exists between tourist guidance and the quality of service in the San Francisco Convent museum”.The sample consisted of 384 visitors to the Museum, it was characterized by gender, age group, the instrument was focused on knowing the level of enthusiasm of the tour guide, the use of some technological equipment in the guide service, the level of attention to mu- seum visitors, ethics and morals of the tour guide to enforce relevant regulations during the on-site visit to safeguard the integrity of the collections.The results obtained determine that the processes that have been used during the development of the service must be impro- ved, two segments of visitors were identified, one of them is interested in knowing about the Museum only the basic and elementary aspects and the other segment is very interested in the technical-artistic aspects of the collections. In order to generate pleasant experien- ces in each of these segments, it is important to develop a manual of administrative proce- dures, as well as a manual for the Tourism Guide of the San Francisco Convent Museum.